PENGARUH MODEL PEMBELAJARAN INKUIRI DAN KEMAMPUAN BERPIKIR KRITIS SISWA TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK LISTRIK DINAMIS DI KELAS X SMA NEGERI 12 MEDAN T.P 2015/2016 - Febrianne, Naibaho Evi; Sinulingga, Karya (JURNAL IKATAN ALUMNI FISIKA, 2016)
This research aims to know the influence of model Inkuiri and critical thinking ability against learning outcomes grade X in Dynamic Electrical material. The population in this research is the whole grade X SMA Negeri 12 Medan. This research sample taken two classes that are defined by means of Cluster Random Sampling. The second class of different treatment namely class experiments with Inkuiri learning model and the control Class with the conventional learning. The instruments used the test results of learning multiple choice with a total of 15 items and tests the ability of critical thinking test descriptions with a total of 8 items was validated. Based on the results of research and data analysis results using the test hypothesis 2 way ANAVA obtained there the influence of the results of the study due to the application of learning models Inkuiri and there is the influence of critical thinking above average with critical thinking under average against student learning outcomes and also there is the interaction between the learning model Inkuiri with critical thinking to improve student learning outcomes.